In the steps of St. Paul - Morton, Henry C. (Dodd, Mead, Co. New York, 1936)
The author describes his travels in the areas where Paul lived and worked.
Chapter one: In which I set out in the steps of St. Paul -- Chapter two: Describes a journey to Damascus -- Chapter three: I enjoy a brief glimpse of Aleppo and Journey to Antioch -- Chapter four: Describes how I sailed to Cyprus in a cargo-boat -- Chapter Five: I revisit Turkey -- Chapter six: In which I describe the sites of Pisidian Antioch -- Chapter seven: Describes a journey to Izmir -- Chapter eight: I stay in Athens and meet a man called Sophocles and another called Byron -- Chapter nine: I follow the steps of St. Paul from Athens to Corinth -- Chronology of St. Pule's life; How St. Paul came to write his epistles; Bibliography; Index
Includes Index
Keywords: Paul; Middle East -- Description and travel; Bible -- New Testament -- Geography